Embryo presence regulates NODAL/LEFTY2 system in the rat oviduct in vivo. Issue 11 (16th August 2019) - Argañaraz, Martin E.; Zampini, Renato; Apichela, Silvana A.; Barraza, Daniela E.; Angiono, Georgina; Lombardo, Daniel
Abstract: To gain further insight in the mechanisms of the embryo–maternal dialog in the oviduct, expression of members of the transforming growth factor‐β superfamily, NODAL, its inhibitor, LEFTY2, and their coreceptor, CFC1, were studied in the oviduct of 3‐day post copula (3 dpc) females with and without embryos (E and NE), pseudopregnant rats (SP3), and in 3‐day embryos. Nodal transcripts in SP3 oviducts showed a steady‐state relative abundance when compared with proestrus stage and the 3 dpc. In contrast, Lefty2 and Cfc1 relative abundance levels in proestrus and 3 dpc were higher. When comparing E with NE oviducts, Nodal and Lefty2 expression levels decreased, while Cfc1 expression increased in the presence of embryos. Nodal messenger RNA (mRNA) was observed in the embryo, but Lefty2 and Cfc1 transcripts were not found. In addition, an increase in Lefty2 expression coincided with increased levels of matrix metalloproteinases 9 mRNA and protein in the oviduct and in the oviductal fluid, respectively. These observations have shed new light on the relevance of the NODAL/LEFTY2 pathway in the oviduct during early embryo development and the role of the embryo in modulating this pathway. Abstract : This work describes the expression of members of the transforming growth factor‐β superfamily, NODAL, LEFTY2, and their coreceptor, CFC1, in the oviduct of rats and the influence of the embryo in their regulation. In addition, a possible function of these genes throughout matrix metalloproteinases 9 is suggested.